Surgical outcomes of tethered cord syndrome in adults versus pediatric patients: A comparative study - Dinesh Shukla; Hari Prakash Rai; Shivam Sharma (Asian Journal of Medical Sciences)
Background: Tethered cord syndrome (TCS) is a neurological disorder caused by the abnormal attachment of the spinal cord, which limits movement and leads to progressive neurological deficits. This study compares the surgical outcomes of TCS in pediatric and adult patients following detethering surgery at Maharani Laxmi Bai Medical College, Jhansi, Uttar Pradesh, between August 2015 and August 2024.